ANALISIS PENERAPAN AKUNTANSI PERKOPERASIAN PADA KOPERASI SIMPAN PINJAM BUDI KARYA LUBUK TERAP SOREK SATU - Dian Saputra; Herliana Wahyuningsih (Journal Of Islamic Finance And Accounting Research, 2023)
This research was conducted at the Savings and Loans Cooperative Budi Karya Lubuk Terap Sorek Satu with the aim of knowing whether the accounting practices used by the Savings and Loans Cooperative Budi Karya Lubuk Terap Sorek Satu were following generally accepted accounting principles. This study uses a descriptive methodology and a qualitative design. Technical analysis uses descriptive qualitative data analysis or data studies that characterize words or sentences and produce conclusions by taking a theoretical and logical approach to the existing subject. The study findings show that cooperatives have not made financial statements and accounting procedures that are transparent. Therefore, it is important to review the methods used in the preparation of financial statements. Transactions, journals, ledgers, trial balances, adjusting journals, worksheets, and financial statements are the first steps in preparing financial statements. After doing the research, it can be concluded that the Savings and Loans Cooperative Budi Karya Lubuk Terap Sorek Satu does not use accounting by generally accepted accounting standards.